A Clinical Audit on the Predictors for Visual Morbidity in Patients with Behçet's Disease Attending Cairo University Hospitals. (2nd April 2020) - Allam, Riham S. H. M.; Medhat, Basma M.
ABSTRACT: Objectives: To study the visual disability predictors in Behçet's disease (BD). Methods: A cross-sectional observational study including 54 patients. Sociodemographic and cumulative clinical characteristics were obtained. Ophthalmic examination focused on disease activity and degree of visual loss. Results: Presenting features included oral ulcers, orogenital ulcers, uveitis, and vascular involvement. Ocular involvement was also present in a majority of the cases 74.1%. The age at onset had no significant effect on diagnostic time lag ( P = .9), unlike rural residency ( P = .02). Laterality, ocular activity, and interventions significantly affected final visual acuity (P˂0.001). A diagnostic time lag ≥ 9 months significantly affected final visual acuity ( P = .039). Conclusion: BD is associated with considerable vision loss at a young age. Panuveitis, bilaterality, ocular activity, and interventions are significant predictors. A diagnostic time lag ≥ 9 months is associated with poor visual outcomes and is significantly associated with rural residency.